2007
DOI: 10.1016/j.nbd.2006.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Preventing polyglutamine-induced activation of c-Jun delays neuronal dysfunction in a mouse model of SCA7 retinopathy

Abstract: We have approached the role of cellular stress in neurodegenerative diseases caused by polyglutamine expansion (polyQ) in the context of Spinocerebellar ataxia type 7 (SCA7) that includes retinal degeneration. Using the R7E mouse, in which polyQ-ataxin-7 is specifically over-expressed in rod photoreceptors, we previously showed that rod dysfunction correlated to moderate and prolonged activation of the JNK/c-Jun stress pathway. SCA7 retinopathy was also associated with reduced expression of rod-specific genes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
10
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 68 publications
4
10
0
Order By: Relevance
“…Retinal ischemia induced by elevation of intraocular pressure leads to activation of JNK and p38 MAP kinases within the first 6 h (Roth et al 2003;Merienne et al 2007;Roduit and Schorderet 2008). Long-term activation of MAP kinases has also been reported in excitotoxic retinal damage, with activation beginning 1-6 h after the NMDA treatment or the ischemic insult (Zhang et al 2002;Munemasa et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Retinal ischemia induced by elevation of intraocular pressure leads to activation of JNK and p38 MAP kinases within the first 6 h (Roth et al 2003;Merienne et al 2007;Roduit and Schorderet 2008). Long-term activation of MAP kinases has also been reported in excitotoxic retinal damage, with activation beginning 1-6 h after the NMDA treatment or the ischemic insult (Zhang et al 2002;Munemasa et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Another group of rats underwent the same surgical procedure for bilateral carotid occlusion (n = 9) or sham operation (n = 5) and retinas were removed after 4 h in order to investigate the signaling pathways that are activated within the first few hours after an ischemic insult (Roth et al 2003;Merienne et al 2007;Roduit and Schorderet 2008). Samples were processed for Western blot analysis as described earlier (Racz et al 2007).…”
Section: Western Blotmentioning
confidence: 99%
“…R7E transgenic mice develop a phenotype earlier than P7E mice, with a pathology that includes NIIs formation, retinal photoreceptor dysfunction, and neurodegeneration (Helmlinger et al, 2004aYefimova et al, 2010;Yvert et al, 2000). Notably, the deactivation of the JNK/c-Jun stress pathway in R7E mice ameliorates retinopathy and may be a promising finding for future therapies (Merienne et al, 2007). In the R7E mouse retina, mutant ataxin-7 alters the recruitment of the SAGA complex to chromatin resulting in H3 hyperacetylation, leading to transcriptional deregulation of rod differentiation and retinopathy .…”
Section: Cell-specific Sca7 Models With Pcp2 (L7) Rhodopsin and Gfamentioning
confidence: 99%
“…Among other therapeutic strategies under investigation for polyQ ataxias are modulation of signal transduction pathways (Merienne et al, 2007), induction of neuroprotective effects with growth factors or stem cell transplantation (Chang et al, 2011a,b;Noma et al, 2012), and modulation of calpain activity (Simões et al, 2012).…”
Section: Therapies For Polyq Diseasesmentioning
confidence: 99%
“…Expression-analysis revealed that nearly all rod-specific genes were affected, leading to visual impairment in SCA7 mice. When these mice were crossed with a knock-in line expressing JUNAA, an alanine-substituted form of jun which is inactive, the retinal phenotype was improved and there was restoration of Nrl, a factor active in transcription of rod-specific proteins [62]. …”
Section: Sca7mentioning
confidence: 99%